Wet etching of GgAs for lateral PIN photodiode - Ahmad, Mohd Hairul Faizal; Shaari, Sahbudin (Penerbit Universiti Sains Malaysia, 2004)
Photodiode play important roles in optical communication systems nowadays. In this field, fiber optic cable is used as an information signal transmission medium between the light sources, sensors and photodiode. Many materials can provided to make the photodiode substrate in order to produce the detector to be used in application that require higher bandwidth and long distance transmission. Therefore, the optical receiver for long-distance telecommunication has primarily been implemented in III-V materials like GaAs or InGaAs in order to achieve the highest possible performance.